2017
DOI: 10.1073/pnas.1715772114
|View full text |Cite
|
Sign up to set email alerts
|

Smek1/2 is a nuclear chaperone and cofactor for cleaved Wnt receptor Ryk, regulating cortical neurogenesis

Abstract: The receptor-like tyrosine kinase (Ryk), a Wnt receptor, is important for cell fate determination during corticogenesis. During neuronal differentiation, the Ryk intracellular domain (ICD) is cleaved. Cleavage of Ryk and nuclear translocation of Ryk-ICD are required for neuronal differentiation. However, the mechanism of translocation and how it regulates neuronal differentiation remain unclear. Here, we identified Smek1 and Smek2 as Ryk-ICD partners that regulate its nuclear localization and function together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…Wnt-Ryk signaling via the planar cell polarity pathway has been previously implicated in neuronal development (Hollis et al, 2016;Lanoue et al, 2017;Macheda et al, 2012;N€ usslein-Volhard and Wieschaus, 1980;Reynaud et al, 2015;Schmitt et al, 2006). A number of other studies have found that translocation of the Ryk intracellular domain to the nucleus in response to Wnt activity directs progenitor cell neurogenesis in the developing dorsal and ventral forebrain (Chang et al, 2017;Kamitori et al, 2005;Lyu et al, 2008;Zhong et al, 2011). Our findings also suggest that Ryk ICD signaling plays an important role in interneuron subtype identity.…”
Section: Discussionsupporting
confidence: 73%
“…Wnt-Ryk signaling via the planar cell polarity pathway has been previously implicated in neuronal development (Hollis et al, 2016;Lanoue et al, 2017;Macheda et al, 2012;N€ usslein-Volhard and Wieschaus, 1980;Reynaud et al, 2015;Schmitt et al, 2006). A number of other studies have found that translocation of the Ryk intracellular domain to the nucleus in response to Wnt activity directs progenitor cell neurogenesis in the developing dorsal and ventral forebrain (Chang et al, 2017;Kamitori et al, 2005;Lyu et al, 2008;Zhong et al, 2011). Our findings also suggest that Ryk ICD signaling plays an important role in interneuron subtype identity.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, as a case study for prioritized RRD mutations, we experimentally validated the effect of an ASD proband de novo noncoding mutation laying outside of a canonical splice site that we predicted to disrupt splicing of SMEK1 (ExAC pLI=1.0; Supplementary Fig. 12), Smek1 has previously been shown to regulate cortical neurogenesis through the Wnt signaling pathway 37 . For this mutation, we observed a >40% reduction in the inclusion of the exon for the ASD proband allele compared to the sibling allele in a minigene assay (Methods), in agreement with the high predicted RRD impact.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shows that nuclear chaperone Smek1/2 can interact with Ryk-ICD. Smek1/2 can mediate Ryk-ICD nuclear localization [ 115 ]. This research indicates that Smek1/2 and Ryk-ICD associate with chromatin to co-occupy regulatory regions of some target genes in order to regulate their expression [ 115 ].…”
Section: Proteolytic Cleavage In Various Members Of Rtkmentioning
confidence: 99%